Ophthalmological follow-up of prematurely born children in preschool age: prospective study of visual acuity, refractive errors and strabismus - Montvilaitė, Donata; Grizickaitė, Agnė; Augytė, Aistė; Skvarciany, Inesa; Barkus, Arūnas; Usonis, Vytautas (Acta medica Lituanica, 2016)
Background. Preterm birth is a very relevant problem. Retinopathy of prematurity in its severe forms causes visual impairment or can lead to blindness. The aim of the present study was to describe the visual outcome in prematurely born and full-term children at the preschool age and to evaluate the effects of prematurity per se, ROP, and treatment on visual acuity and refractive errors. Materials and methods. A prospective study on the incidence of ROP during 2006–2008 included 103 preterm infants. 81 had ROP and 22 had no history of ROP; 40 were age-matched healthy children. All underwent a complete ophthalmic examination. Results. Significant myopia (≤  –0.50D) in prematurely born children differed from full-term ones. The  ROP treated group had the  highest prevalence of myopia (P  2D) was dominant in the premature group (39%) as compared with the  control group (0%) (P
Keywords: preterm birth; retinopathy of prematurity; treatment; visual impairment